Surface water dependencies and activity patterns of mammalian herbivores in South Africa - Padayachy, Janiel (University of the Witwatersrand, Johannesburg, 2024)
An increase in aridity in Africa may make water availability more variable, thus understanding how animals respond to these conditions is important for future wildlife management and conservation. However, mammalian herbivores with varying water requirements may respond differently to changes in water availability and predation. Using camera trap data, I analysed the spatial distribution relative to surface water sources and the 24-hour activity of 16 mammalian herbivores across 10 sites in South Africa. As expected, water dependent herbivores were generally closer to water, but only at sites where lions were absent. Herbivores with low water requirements were more nocturnal, potentially reducing water required to cool themselves evaporatively when active during the heat of the day. But that nocturnal activity was reduced when lions were present, likely reducing predation risk, increasing water requirements to dissipate heat and forcing herbivores to remain close to water. Nocturnal activity increased with body size in mixed-feeders and grazers, but decreased with body size in browsers, potentially reflecting more time spent foraging by large browsers. Using a novel approach of multistate diel occupancy models I showed that herbivores were generally active during both the day and night, and that the presence of lions impacted occupancy of preferred prey species (blue wildebeest, gemsbok and zebra). Diel occupancy of water-dependent prey (blue wildebeest) was influenced by an interaction between lion presence and distance to water sources. Thus environmental factors as well as physiological and morphological features affected the timing of activity and spatial distribution of several mammalian herbivore species in South African wildlife areas, which should be considered for future research and management of these species.
A dissertation submitted in the fulfilment of the requirements for the degree Master of Science (Dissertation), to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Mammalian herbivore; Surface water dependence; Diel activity; Diel occupancy; Predation risk; Camera traps; UCTD; SDG-6: Clean water and sanitation; SDG-15: Life on land